Spatial-temporal variation characteristics of cultivated land and controlling factors in the Yangtze River Delta region of China - Huo, Kun; Ruan, Yunfeng; Fan, Haizhou; Guo, Chunhui; Cai, Hong (Frontiers in Environmental Science, 2022)
Comprehending the change characteristics and controlling factors of regional cultivated land resources is one of the important preconditions for their healthy development. The main objective of this study is to analyze the spatial–temporal variation characteristics of cultivated land and controlling factors in the Yangtze River Delta region. Thus, the mathematical–statistical, land use dynamic degree model, principal component analysis, and geographically weighted regression model were used to analyze the change in cultivated land area and social–economic factors in the Yangtze River Delta region from 2009 to 2018. The results showed that the cultivated land area and per capita cultivated land area had a decreasing trend from 2009 to 2018, decreasing by 8.5 × 104 ha and 0.0039 ha, respectively. From the perspective of spatial patterns, the rapidly decreasing areas of cultivated land were mainly distributed in the southeast, while the slowly decreasing areas of cultivated land were becoming concentrated in the northwest, and the slowly increasing areas presented as scattered distribution, which was also the same spatial distribution for the per capita cultivated land area in the Yangtze River Delta region. Among these factors, population (POP) and the total power of agricultural mechanization (TPAM) had a positive spatial correlation with cultivated land. The gross domestic product (GDP) had a negative spatial correlation with cultivated land, which revealed that cultivated land was intensely affected by human activities. Moreover, the spatial distribution and influence degree of the controlling factors differed in regions. Our research is expected to reveal the relationship between economic development and cultivated land protection for providing references for strengthening regional cultivated land management, maintaining the healthy development of regional resources, and rational utilization of cultivated land.